Karate kid : legends [videorecording (DVD)] - Lieber, Rob, 1976-; Cheng, Long, 1954-; Wang, Ben, 2000-; Jackson, Joshua, 1978-; Stanley, Sadie, 2001-; Ming-Na, 1963-; Oleff, Wyatt, 2003-; Knight, Aramis, 1999-; Macchio, Ralph, 1961-; Brown, Justin (Cinematographer); Lewis, Dominic; Gordon-Crozier, Mirren (Sony Pictures Home Entertainment, 2025)
"When kung fu prodigy Li Fong relocates to New York City with his mother to attend a prestigious new school, he finds solace in a new friendship with a classmate and her father. But his newfound peace is short-lived after he attracts unwanted attention from a formidable local karate champion. Driven by a desire to defend himself, Li embarks on a journey to enter the ultimate karate competition. Guided by the wisdom of his king fu teacher, Mr. Han, and the legendary Karate Kid, Daniel LaRusso, Li merges their unique styles to prepare for an epic martial arts showdown."--